Aeroecology 2017
DOI: 10.1007/978-3-319-68576-2_3
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Habitat Concept to the Airspace

Abstract: Habitat is one of the most familiar and fundamental concepts in the fields of ecology, animal behavior, and wildlife conservation and management. Humans interact with habitats through their senses and experiences and education to such a degree that their perceptions of habitat have become second nature. For this reason, it may be difficult at first to accept the airspace as habitat, an area that is invisible, untouchable, highly dynamic, and its occupants difficult to see. Nonetheless, the habitat concept, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 106 publications
0
13
0
Order By: Relevance
“…Only relatively recently has the technology become an accepted remote sensing tool for studying ecology of the airspace (Diehl et al. ). Our study demonstrates the possibility of using adult mayfly swarms measured via radar as a means to quantify aerial invertebrate abundance with high temporal resolution (e.g., 4–10 min scan intervals) and spatial resolution (e.g., 0.25–1 km) over an expansive area.…”
Section: Discussionmentioning
confidence: 99%
“…Only relatively recently has the technology become an accepted remote sensing tool for studying ecology of the airspace (Diehl et al. ). Our study demonstrates the possibility of using adult mayfly swarms measured via radar as a means to quantify aerial invertebrate abundance with high temporal resolution (e.g., 4–10 min scan intervals) and spatial resolution (e.g., 0.25–1 km) over an expansive area.…”
Section: Discussionmentioning
confidence: 99%
“…Migrating birds might modify flight altitudes in response to the air pollution of urban areas. Research about the effects of air pollution in the environment and in birds, however, has focused mostly on terrestrial and aquatic habitats (reviewed in Lovett et al, ), and on on‐the‐ground specimens (reviewed in Sanderfoot & Holloway, ), research is needed to evaluate its effects on airspace habitat use (Diehl, Peterson, Bolus, & Johnson, ) and bird behaviour aloft (but see Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Anthropogenic noise masks bird calls, forcing them to call in higher frequencies and reducing occupancy of otherwise suitable habitat by species sensitive to loud sources of noise (reviewed in Ortega, ; Shannon et al, ). It has been suggested that anthrophony may be a source of information that birds use to avoid certain habitats (Mullet et al, ), and this effect may extend upwards, towards the airspace habitat (sensu Diehl, ; Diehl et al, ). Thus, migrating birds may modify their flight altitudes due to an effect of anthrophony‐dominated soundscapes, which likely represent non‐habitat and complicate communication.…”
Section: Discussionmentioning
confidence: 99%
“…Recent recognition that parts of the airspace may, at least temporarily, also represent important habitat for flying animals suggests the need to also identify airspaces critical to populations of flying animals and possibly establish aerial reserves. For example, traditional feeding or migratory flight corridors or airspaces proximal to large bat or bird roosts, may require preservation (no wind turbines, power lines, lit buildings or other man-made obstacles) or some other form of legal protection (Diehl 2013, Lambertucci et al 2015, Diehl et al 2018. Such reserves could benefit migratory birds and bats moving through geographic and seasonal bottlenecks (Rydell et al 2014, Bayly et al 2017, Panuccio et al 2018, Sherry 2018 or more locally, roosting birds and bats or foraging waterfowl and raptors that use the same airspaces on a recurring basis.…”
Section: Identification and Management Of Conservation Areasmentioning
confidence: 99%
“…Given the high risk to many key stopover sites for threatened migratory species globally (for example tidal mudflats along the Yellow Sea; Studds et al 2017), radar will play an increasingly important role in assessing the value of these areas for the species they support. WSRs, along with other radar methods may also quantify bird and bat movements in ways that identify airspaces important to species conservation but are also reliant on supporting methodologies to elucidate species composition (Diehl et al 2018).…”
Section: Identification and Management Of Conservation Areasmentioning
confidence: 99%